'Listen to the story': narrative and song in Rāmcand Bālak's Sītācarit, a Jain Rāmāyaṇa in Brajbhāṣā. (3rd April 2019) - Plau, Adrian
ABSTRACT: This article explores the different modes of song in the Sītācarit, a seventeenth-century Brajbhāṣā telling of the Jain Rāmāyaṇa, and suggests a general understanding of the relationship between song and narrative that sees the songs as constituting an added narrative layer. It notes how the modes of song in the Sītācarit evoke different performative settings and aesthetic influences, ranging from the educational to the courtly, and suggests how the intertwining of narrative and song lets us glimpse the poetics of devotion through the lens of the circulation of literary and devotional trends in early modern North India.